Transcription Factors Involved in the Development and Prognosis of Cardiac Remodeling - Hong, Jia-Hui; Zhang, Hai-Gang (Frontiers in Pharmacology, 2022)
To compensate increasing workload, heart must work harder with structural changes, indicated by increasing size and changing shape, causing cardiac remodeling. However, pathological and unlimited compensated cardiac remodeling will ultimately lead to decompensation and heart failure. In the past decade, numerous studies have explored many signaling pathways involved in cardiac remodeling, but the complete mechanism of cardiac remodeling is still unrecognized, which hinders effective treatment and drug development. As gene transcriptional regulators, transcription factors control multiple cellular activities and play a critical role in cardiac remodeling. This review summarizes the regulation of fetal gene reprogramming, energy metabolism, apoptosis, autophagy in cardiomyocytes and myofibroblast activation of cardiac fibroblasts by transcription factors, with an emphasis on their potential roles in the development and prognosis of cardiac remodeling.